2014 IEEE International Electron Devices Meeting 2014
DOI: 10.1109/iedm.2014.7047157
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of directed ion beams from doping to materials engineering

Abstract: We review recent changes to implanter processing capabilities, including the adoption of cryogenic implants to reduce leakage and contact resistance as well as high temperature implants for finFETs. We discusss some specific 3D challenges and introduce a new process technology for 3D that uses directed ion beams for material modification including implant, etch and deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Plasma doping is a candidate technology for meeting these requirements. [8][9][10][11][12][13][14][15] Ueda et al reported high activated dose arsenic (As) conformal doping of 10 to 40 nm (aspect ratio > 2-4) silicon (Si) fin structures using a microwave RLSA™ plasma source using a radial line slot antenna and an AsH 3 gas process. 12) The source facilitates doping by supplying low energy ions and dopant radicals to the substrate ensuring minimum physical damage.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma doping is a candidate technology for meeting these requirements. [8][9][10][11][12][13][14][15] Ueda et al reported high activated dose arsenic (As) conformal doping of 10 to 40 nm (aspect ratio > 2-4) silicon (Si) fin structures using a microwave RLSA™ plasma source using a radial line slot antenna and an AsH 3 gas process. 12) The source facilitates doping by supplying low energy ions and dopant radicals to the substrate ensuring minimum physical damage.…”
Section: Introductionmentioning
confidence: 99%